The Investigation of Job Search Behaviour Among Workers in the Manufacturing Sector in Malaysia: Do Education and Skill Mismatch Matter - Zainizam Zakariya; Norimah Ramli; Shahrun Nizam Aziz; Norasibah Jalil; Nurul Sharniza Husin (International Journal of Supply Chain Management, 2020)
This paper investigates the influence of education and skill mismatch on job search behaviour and quits intention among workers in the manufacturing sector in Malaysia. Three indicators of mismatch were employed here; over-education, overskilling and job mismatch and they were measured using workers’ own assessment. Using data from own field survey, the 2016 Co-workers’ Externalities at Workplace (TERS-16), it was found that 18%, 45% and 37% of respondents were deemed overeducated, overskilled and being in mismatched jobs, respectively. Using random effect probit models, three main findings were observed. As expected, there was strong evidence that overqualification resulted in job search activity. Being in jobs that completely different from workers’ actual field of study also increased the likelihood of seeking new jobs relative to the reference group. Finally, being overskilled also led to a higher probability of being engaged in job search behaviour. Interestingly, the magnitude of the effect was twice higher for the severely than for the moderately-overskilled. These findings were robust even after all education-skill mismatch indicators were controlled for together. The results of the study reflect greater potential mobility amongst the mismatched workers in Malaysia. There is impossible to ascertain whether or not such a move results in improved matches due to data limitation. Yet, from a firm’s perspective, higher intensity of job search behaviour among the mismatched may lead to a higher turnover rate and incur hiring and training cost.